Genetic Data Sharing in the European Health Data Space: An Urgent Call for Coordinated Action by the Member States (BioLaw Journal - Rivista di BioDiritto, 2026)
In the European Health Data Space, there are still loose ends to be tied up. Regarding the secondary use of genetic data, the failure of Member States to reach a consensus during the EHDS negotiations led to a regulatory exception. Once again, in application of Article 9(4) GDPR, Member States may introduce additional safeguards for the secondary processing of genetic data in the EHDS. This paper analyses the risks of this exception for genetic research and personalised medicine, while proposing policy alternatives that would allow Member States to enhance institutional control over the genetic data lifecycle and boost individual autonomy and trustworthiness.
Keywords: EHDS; genetics; opt-in; opt-out; consent; EDIC